كتاب "أعيان البيان" لحسن السندوبي: دراسة وصفية تحليلية - عبدالرحمن، إيمان سعد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This is an analytical and critical study of the book "A'ayan Albayan" by the author, Hasan Alsandoobi. This research focuses on the writings of the twelve poets and authors who are mentioned in the book. Moreover, it highlights the views of Hasan Alsandoobi and the critics of his opinion. The study describes Hasan Alsandoobi and his most important contributions to the enrichment of Arabic poetry and prose. It sheds light on the artistic value of literature of the 13th century AH. It also deals with Alsandoobi's approach in writing biographies. The study also deals with the standard criticisms for Hasan Alsandoobi and his thoughts on Arabic literature. The researcher used descriptive, analytical and historical methods to achieve the research objectives. The study concludes with the following: Hassan Alsandoobi has many contributionsto enrich the Arabic poetry and prose. He has created criteria for selection of author such as combining poetry and prose, diversity in poetry and writing purposes,diversity in the form of the poem and its construction and the quality in poetry and prose.